RELIGIOUS TOLERANCE LIMITS: A SEMIOTIC LINGUISTIC ANALYSIS OF AL-KĀFIRŪN CHAPTER: - Supardi Supardi (Leksema: Jurnal Bahasa dan Sastra, 2022)
This article aims to find the demarcation limit lines of religious tolerance from al-Kāfirūn chapter of the Holy Qur’an and respond to some issues developing in Indonesian. This study is based on an exploratory analysis of semiotic linguistic meanings of the chapter with an intention to respond to Indonesian Issues regarding the practices of religious greeting of the opening public speech, congratulating other religious celebrations, and singing performance of muslim students’ in a church as cases in point. This study found that the religious tolerance limits are ‘the belief’ and ‘the rituals’. Three activities are considered to go beyond the religious tolerance limits drawn from the chapter being studied, namely: (1) compromising religious belief, (2) mixing religious ritual activities, and (3) imposing religion on others. These three are, among others, the measurement of the activities considered tolerance or intolerance.